Peran Teknologi dalam Mengurangi Konflik Bahasa: Tinjauan Solusi Digital - Khoiroh, Himmatul (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2023)
Purpose- This research aims to explore the impact of highly advanced technology in reducing cross-cultural language conflicts, especially in Indonesia, which boasts rich linguistic and cultural diversity. Information technology has significant potential to serve as a catalyst in mitigating language conflicts amid the cultural and linguistic diversity in Indonesia. Design/Methodology/Approach- The research employs a descriptive-analytical literature review method, which highlights various relevant theories supporting an understanding of how technology can play a crucial role in dampening language conflicts. Data collection from literature reviewed by several researchers is conducted to gain a profound understanding of the impact of information technology in mitigating language conflicts among different language and cultural groups. Findings- The findings indicate that information technology serves not only as a tool to reduce conflicts among groups with different linguistic and cultural backgrounds but also as a facilitator in building intercultural and interreligious communication. By exploring digital solutions, it is evident that technology plays a significant role in deepening cross-cultural understanding and strengthening inter-country relationships. With technological advancements, it is expected that these solutions will continue to innovate and contribute to creating a more inclusive and mutually understanding society amidst the linguistic and cultural diversity in Indonesia. Research Limitation/Implications- This research is still in the theoretical realm and does not involve field testing as a comparative method. Nevertheless, this study can be considered as a preliminary step in exploring the role of rapidly developing technology in addressing language conflict issues.